Commensal symbiosis between agglutinated polychaetes and sulfate‐reducing bacteria. Issue 3 (17th March 2014) - Guido, A.; Mastandrea, A.; Rosso, A.; Sanfilippo, R.; Tosti, F.; Riding, R.; Russo, F.
Abstract Pendant bioconstructions occur within submerged caves in the Plemmirio Marine Protected Area in SE Sicily, Italy. These rigid structures, here termed biostalactites, were synsedimentarily lithified by clotted‐peloidal microbial carbonate that has a high bacterial lipid biomarker content with abundant compounds derived from sulfate‐reducing bacteria. The main framework builders are polychaete serpulid worms, mainly Protula with subordinate Semivermilia and Josephella. These polychaetes have lamellar and/or fibrillar wall structure. In contrast, small agglutinated terebellid tubes, which are a minor component of the biostalactites, are discontinuous and irregular with a peloidal micritic microfabric. The peloids, formed by bacterial sulfate reduction, appear to have been utilized by terebellids to construct tubes in an environment where other particulate sediment is scarce. We suggest that the bacteria obtained food from the worms in the form of fecal material and/or from the decaying tissue of surrounding organisms and that the worms obtained peloidal micrite with which to construct their tubes, either as grains and/or as tube encompassing biofilm. Peloidal worm tubes have rarely been reported in the recent but closely resemble examples in the geological record that extend back at least to the early Carboniferous. This suggests a long‐lived commensal relationship between some polychaete worms and heterotrophic, especially sulfate‐reducing, bacteria.